ANALISIS PERBANDINGAN PEMAMPATAN DATA TEKS DENGAN MENGGUNAKAN METODE HUFFMAN DAN HALF - BYTE - Supiyandi Supiyandi; Okta Frida (Universitas Islam Negeri Sumatera Utara, 2018)
Generally the use of conventional methods in data compression can not overcome the performance of data manipulation in saving memory usage and speed in data communications. Using a new manipulation method that applies the Huffman compression algorithm and the Half-Byte alphabet can compress data from the user interface before it is stored in the repository, so performance in manipulating the data will be better. With the new method applied to an application software using programming language. Which of the two types of algorithms has a larger ratio (ratio) as a benchmark in the performance of data manipulation. With good performance, it will be able to save the use of memory space on the repository and fast in transmitting data in communicate between the user interface with the repository in the data manipulation.